A fuzzy FMEA for detecting the risk of defects in polyethylene (PE) film products - Erni Krisnaningsih; Imam Ribowo Sakti; Saleh Dwiyatno; Asep Ridwan (Universitas Sultan Ageng Tirtayasa, 2022)
Product quality is a top priority that must be considered so that the products produced follow quality standards based on the characteristics and specifications set by the company. This study aims to identify the failure risk of the most dominant type of defect in Polyethylene (PE) Film products and identify the significant factors that cause the most dominant defects so that a proposal for improvement is obtained. The Fuzzy Failure mode and effect analysis (FFMEA) method is applied to reduce the risk of product defects in the PE Film production process. The steps with FFMEA are: a). Identify the type of defect of the Polyethylene film product, b). investigate the potential causes of each mode of failure and their impact, c). Identify the scale and linguistic terms for the input factors S, O, and D. d). Create a membership function appropriate for S, O, and D input factors, e). Change the input factor values S, O, and D to linguistic variables, f). establish an IF-Then rule, create a fuzzy risk priority number (FRPN) membership function, g). defuzzification. The results showed that the application of this method was quite effectively applied, the risk factor for the dominant defect in the production of PE film was the type of Pinhole defect caused by material factors, and the production process and temperature with proposed improvements were focused on periodic maintenance.